ChemInform Abstract: Magnetic Nanoparticles (CoFe2O4)‐Supported Phosphomolybdate as an Efficient, Green, Recyclable Catalyst for Synthesis of β‐Hydroxy Hydroperoxides. Issue 16 (22nd April 2014) - Li, Pei‐He; Li, Bao‐Le; An, Zhi‐Min; Mo, Li‐Ping; Cui, Zhen‐Shui; Zhang, Zhan‐Hui
Abstract Interestingly, the substitution of epoxides (I) and (III) exerts a significant effect on the ring‐opening direction.